PENGARUH KUALITAS AUDIT TERHADAP COST OF EQUITY CAPITAL (STUDI EMPIRIS PADA PERUSAHAAN YANG YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011) - Pangestika Ayu Aji Kirana; Herry Laksito (Diponegoro Journal of Accounting, 2013)
This research aims to examine the evidence about relationship between audit quality and cost of equity capital in Indonesia. This research  was conducted by using independent variables are audit firm size, audit tenure, auditor industry specialization as audit quality’s proxy. Dependent variable, cost of equity capital calculated with P/E ratio.This research was conducted by regression test as a test of the hypothesis. Data collection in this research using purposive sampling to companies listed at the Indonesian Stock Exchange in 2011. As many as 176 companies are used as samples in this research.Result of this research showed that audit firm size not significantly influence the cost of equity capital. It means that higher audit firm size  not decrease cost of equity capital. Meanwhile, audit tenure and auditor specialization industry significantly influence the  cost of equity capital.